2018
DOI: 10.1371/journal.pone.0201880
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the cellular E3 ubiquitin ligase SIAH-1 and the viral immediate-early protein ICP0 enables efficient replication of Herpes Simplex Virus type 2 in vivo

Abstract: Herpes Simplex Virus type 2 (HSV-2) is a neurotropic human pathogen. Upon de novo infection, the viral infected cell protein 0 (ICP0) is immediately expressed and interacts with various cellular components during the viral replication cycle. ICP0 is a multifunctional regulatory protein that has been shown to be important for both efficient viral replication and virus reactivation from latency. In particular, as previously demonstrated in transfected tissue culture models, ICP0 interacts with the cellular E3 ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Strikingly, levels of AFF4 protein were induced in cells infected with HSV, suggesting that a virus-mediated mechanism might enhance SEC levels for HSV gene expression. Interestingly, reports from the Hauber laboratory have shown that the ICP0 viral IE protein interacts with SIAH1 through SIAH1-binding consensus motifs and that viruses with mutations in these motifs are defective for growth in culture and in vivo (56,57). The authors propose several models, including one in which ICP0 functions to sequester SIAH1, thus blocking SIAH1's interactions with its targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, levels of AFF4 protein were induced in cells infected with HSV, suggesting that a virus-mediated mechanism might enhance SEC levels for HSV gene expression. Interestingly, reports from the Hauber laboratory have shown that the ICP0 viral IE protein interacts with SIAH1 through SIAH1-binding consensus motifs and that viruses with mutations in these motifs are defective for growth in culture and in vivo (56,57). The authors propose several models, including one in which ICP0 functions to sequester SIAH1, thus blocking SIAH1's interactions with its targets.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies identified SIAH1 as an interaction partner for the HSV IE protein ICP0 and demonstrated that a recombinant virus with a mutant ICP0 that did not interact with SIAH1 was defective in growth in vitro and in vivo (56,57). Therefore, to determine if ICP0 was involved in the regulation of AFF4 protein levels upon infection, cells were infected with wild-type (WT) HSV or a recombinant lacking ICP0 (ΔICP0 [58,59]).…”
Section: Suppression Of Hsv Ie Gene Expression and Lytic Infection By Inhibition Of The Secmentioning
confidence: 99%
“…SLSs 1-7 (aa 164-167, 176-179, 331-334, 362-363, 651-654, 664-667 and 678-681, respectively) are indicated with black vertical half-moons ( Boutell et al, 2011 ); SLS4 and aa 634-719 influence PML-NB localization (highlighted grey; ( Everett et al, 2014 )). SIAH binding motif (aa 401-410; ( Czechowicz et al, 2018 )), a NLS (aa 500-506), and USP7 binding motif (aa 620-624) are indicated with vertical rectangles. ICP0 regions of SUMO2/3 (aa 241-388, highlighted orange) and SUMO1 (aa 594-775, highlighted red) binding shown ( Boutell et al, 2011 ; Everett et al, 2014 ).…”
Section: Hsv-1 Interacts With and Hijacks The Host Ubiquitin Machinermentioning
confidence: 99%
“…The characteristics of the SIPs have also been studied (13). A consensus Pro-X-Ala-X-Val-X-Pro (VxP, core sequence; where X is not conserved) motif is common to a family of SIPs (Table I) (11,14,21,(23)(24)(25)(26). Some SIPs are also substrates of Siah1 and are targeted by Siah1 for degradation or functional modification.…”
Section: Structure Of Siah1 and Characteristics Of Siah1-interacting ...mentioning
confidence: 99%